2D Ruddlesden–Popper perovskite sensitized SnP2S6 ultraviolet photodetector enabling high responsivity and fast speed. Issue 1 (25th November 2022) - Zhang, Yue; Wang, Fakun; Zhao, Xuan; Feng, Xin; Zhang, Na; Xia, Fangfang; Ma, Ying; Li, Huiqiao; Zhai, Tianyou
Abstract : A hybrid SnP2 S6 /(PEA)2 PbI4 photodetector with high responsivity and fast response time is developed, which is promising for multiple optoelectronic applications. Abstract : As the newly developed wide-bandgap semiconductors, two-dimensional layered metal phosphorus chalcogenides (2D LMPCs) exhibit enormous potential applications in ultraviolet (UV) photodetection due to their superior optoelectronic performance. However, 2D LMPC-based UV photodetectors generally suffer from low responsivity and slow response speed, which hinder their practical applications. Here, we present an effective strategy of sensitizing 2D LMPC UV photodetectors with a 2D Ruddlesden–Popper (RP) perovskite to enable high responsivity and fast response speed. As a demonstration, a hybrid heterojunction composed of RP perovskite (PEA)2 PbI4 and a 2D SnP2 S6 flake is fabricated by spin-coating method. Benefitting from the strong optical absorption of (PEA)2 PbI4 and the efficient interfacial charge transfer caused by the favorable type-II energy band alignment, the as-fabricated 2D SnP2 S6 /(PEA)2 PbI4 hybrid heterojunction photodetectors show high responsivity (67.1 A W −1 ), large detectivity (2.8 × 10 11 Jones), fast rise/delay time (30/120 μs) and excellent external quantum efficiency (22825%) at 365 nm. Under field-effect modulation, the responsivity of the heterojunction photodetector can reach up to 239.4 A W −1, which is attributed to the photogating mechanism and reduced Schottky barriers. Owing to the excellent photodetection performance, the heterojunction device further shows superior imaging capability. This work provides an effective strategy for designing high-performance UV photodetectors toward future applications.